Community perceptions of health and chronic disease in South Indian rural transitional communities: a qualitative study - Arabella K. M. Hayter; Roger Jeffery; Chitra Sharma; Audrey Prost; Sanjay Kinra (Taylor & Francis Group, 2015)
Background: Chronic diseases are now the leading cause of death and disability worldwide; this epidemic has been linked to rapid economic growth and urbanisation in developing countries. Understanding how characteristics of the physical, social, and economic environment affect behaviour in the light of these changes is key to identifying successful interventions to mitigate chronic disease risk. Design: We undertook a qualitative study consisting of nine focus group discussions (FGDs) (n=57) in five villages in rural Andhra Pradesh, South India, to understand people's perceptions of community development and urbanisation in relation to chronic disease in rural transitional communities. Specifically, we sought to understand perceptions of change linked to diet, physical activity, and pollution (because these exposures are most relevant to chronic diseases), with the aim of defining future interventions. The transcripts were analysed thematically. Results: Participants believed their communities were currently less healthy, more polluted, less physically active, and had poorer access to nutritious food and shorter life expectancies than previously. There were contradictory perceptions of the effects of urbanisation on health within and between individuals; several of the participants felt their quality of life had been reduced. Conclusions: In the present study, residents viewed change and development within their villages as an inevitable and largely positive process but with some negative health consequences. Understanding how these changes are affecting populations in transitional rural areas and how people relate to their environment may be useful to guide community planning for health. Measures to educate and empower people to make healthy choices within their community may help reduce the spread of chronic disease risk factors in future years.